Political entanglements between Pakistan and Kuwait: the transnational figuration of migration, development and charity - Antía Mato Bouzas (Arabian Humanities)
This article examines interactions between Pakistan and the Gulf region with a focus on a case study of mobilities between the southern part of Gilgit-Baltistan (Baltistan), in north-eastern Pakistan, and the state of Kuwait. Moving away from state approaches, this study examines a transnational figuration formed by migrants and religious leaders from Baltistan and members of the Kuwaiti merchant class as a way to ground an understanding of this transnational engagement and its transformative character, mainly for Baltistan but also for Kuwait. Gilgit-Baltistan is a disputed territory and state presence is marginal. The relative absence of the state creates a situation in which people feel the need to fend for themselves. In this context, foreign development and charity work can become a source of empowerment. The Gulf, and concretely, Kuwait exercises an influence in Baltistan via migration, development and charity work.The study of this transnational figuration unfolds how social norms (in terms of a political culture), status, power and social capital help to shape politics in this region of north-eastern Pakistan. Indirectly, this figuration reveals the relatively influential role exercised by the Gulf and, in this case Kuwait, in other regions through a soft diplomacy of development and charity work, but one that has results in political empowerment of this border area of Pakistan. It also shows that this ‘foreign’ activity of Kuwaiti actors responds to forms of seeking political empowerment at home.